(untitled) (Czech Journal of International Relations, 1994)
Among the "domestic" determinants of Germany’s international role and its foreign policy, its complete unification emerges as the most important task. Germany was united politically; but the material and mental division between its western and eastern parts has yet to be overcome. The magnitude of this task is shown by the following few numbers. In 1991, total requirements in East Germany were almost twice the gross domestic product, and this ratio has not changed since then. The differences were balanced by transfers from West Germany, which reached 5-6% of West German GDP. The real level of unemployment in East Germany (taking into account retraining and the creation of new job opportunities, as well as to work on forced reduced working hours) is at least 35%, although the growth in 1992 was 9.7% and in 1993 it was 6.3%. This growth was mainly the result of a boom in the construction industry, as well as the expansion of services and small businesses. The critical task is to remove the East German economy’s dependence on government funding and create a self-sustaining recovery. This can only be achieved if the mass deindustrialization of East Germany is stopped and a competitive new industrial sector.